Susceptibility profiles of bacterial pathogens causing community-acquired urinary tract infections - Atshan, Salman Sahab; Salah, Zohier B; Al-Zihiry, Khalid Jameel Kadhim; Ali A., Alreshidi Mateq; Hamat, Rukman Awang (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Uncontrolled empirical treatment of urinary tract infections (UTIs) has negative aspect on predict- ing the emergence of antimicrobial resistance and knowledge of those patterns has become extremely important from time to time. Therefore, the aim of the present study was to check the prevalence and resistance patterns of uropathogens in the community acquired UTIs. Methods: A total of 7132 urine samples were combined from male 3131 (43.9%) and female 4001 (56.1%) outpatients suspected of having UTIs, respectively over a three-year period and cultured on routine culture media. The bacteria have been identified using basic biochemical tests, and sen- sitivity to various antibiotics was determined by the method of disk diffusion. Results: Of 7132 urine samples 797 (11.2%) yielded significant uropathogens. Among the bacterial species, Escherichia coli was the major causative agent of UTIs for both gender (63.7%), followed by Klebsiella spp (20.8%), Enterococcus faecalis (5.3%), Pseudo- monas spp (4.1%), Proteus spp (3.1%), Enterobacter spp (1.5%), Candida albicans (0.6%), Staphylococcus sapro- phyticus (0.5%), Providencia spp (0.1%) and Staphylococcus aureus (0.1%). The antibacterial sensitivity testing for E. coli, to commonly used antibiotics were showed variable resistant as follows: Ampicilln (78%), Amoxicillin (71%), trimethoprim sulfamethoxazole (42%), Amox/clav. (14%) gentamicin (20%), nitrofurantoin (11%), nalidixic acid (22%), ciprofloxacin (20%), Imipenem (16%),Ceftazidim (26%),Cefotaxim (25%),Ceftriaxon (21%),Cefuroxim (33%). Conclusions: The findings showed that antimicrobial resistance patterns of uropathogens in variable, and continuous monitoring of resistance patterns by using of antibiotic susceptibility testing in the laboratory is the most appropriate to treat UTIs rather than the choice of UTIs empirical treatment.